Heterosis and combining ability in small fruited ash gourd (Benincasa hispida) - KUTTY, C NARAYANAN; SREELATHA, U (The Indian Journal of Agricultural Sciences, 2018)
An attempt was made to develop small fruited ash gourd [Benincasa hispida (Thunb) Cogn] hybrids by crossing 10 genetically diverse ash gourd genotypes in a diallel mating system. The 45 F1 hybrids along with their parents were evaluated for assessing their heterosis and combining ability for 11 important economic traits. The parent P2 (Elevenchery local) was the best general combiner for fruit yield and fruits/plant. The specific combining ability component of variance (∂2s) was higher than general combining ability component of variance (∂2g) for the all the 11 characters studied which indicated the predominance of non-additive gene action in the improvement of these characters. The hybrids, viz. P2 × P7 (Elevenchery local × Chengamanad) which exhibited the highest heterosis over top parent (79.95 %) and highly significant sca effects for fruit yield, fruit length, flesh thickness, average fruit weight and days to first fruit harvest followed by P3 × P4 (Malappuram × IC 392313) which recorded the highest heterosis over better parent (166.38%) and highly significant sca effects for fruit yield, fruits/plant, flesh thickness and fruit length were found promising. Both the hybrids were small fruited with average fruit weight (2.04 kg) and (1.65 kg) respectively.